Characterizing the Role of HuR in Skeletal Muscle of Mice with Spinal Muscular Atrophy - Haghandish, Amir (Université d'Ottawa / University of Ottawa, 2017)
Spinal muscular atrophy (SMA) is a debilitating neuromuscular disorder characterized by insufficient SMN protein, resulting in motoneuron death. Initially, it was thought that motoneuronal death is followed by muscle atrophy; however, recent research is beginning to reveal possible muscle intrinsic defects, independent of motoneuron defects, in SMA. Previous studies have elucidated the cooperative involvement of CARM1, HuD and SMN in motoneurons, revealing HuD as a possible key player in the SMA phenotype. In this study, we focus on HuR, a ubiquitous family member of HuD, and the possibility that it plays a similar key role with CARM1 and SMN in skeletal muscle. Through the use of an shCARM1 stable line of C2C12s, we show that CARM1 is necessary for HuR functionality during differentiation. We further show that the methylation of HuR is necessary for its capability to translocate cytoplasmically during differentiation. We confirm an interaction between HuR and SMN, suggestive of a similar mechanism as was shown previously with HuD. In light of these findings, we next progressed to determine whether HuR is misregulated in an SMA mouse model. We report increased CARM1 levels in skeletal muscles of these mice. We further discovered that a deficiency in SMN protein impairs HuR upregulation and cytoplasmic translocation in response to HuR activation through sciatic nerve denervation. These findings were correlated with aberrant mRNA expression of HuR targets upon denervation. Taken together, these results show that HuR methylation is essential for proper myogenesis, and that the mechanism by which it acts likely requires sufficient SMN protein levels. In a deficiency of SMN, HuR shows signs of misregulation that may play a role in the inability to maintain or repair muscle in SMA.
Keywords: Spinal Muscular Atrophy; HuR; CARM1; SMA; Skeletal Muscle; Differentiation